Is Scheduled Intravenous Acetaminophen Effective in the Pain Management Protocol of Geriatric Hip Fractures?. (September 2015) - Bollinger, Alexander J.; Butler, Paul D.; Nies, Matthew S.; Sietsema, Debra L.; Jones, Clifford B.; Endres, Terrence J.
Background: Hip fractures have significant effects on the geriatric population and the health care system. Prior studies have demonstrated both the safety of intravenous (IV) acetaminophen and its efficacy in decreasing perioperative narcotic consumption. The purpose of this study is to evaluate the effect of scheduled IV acetaminophen for perioperative pain control on length of hospital stay, pain level, narcotic use, rate of missed physical therapy (PT) sessions, adverse effects, and discharge disposition in geriatric patients with hip fractures. Methods: A retrospective review was performed of all patients 65 years and older admitted to a level I trauma center, who received operative treatment for a hip fracture over a 2-year period. Demographic data, in-hospital variables, and outcome measures were analyzed. Three hundred thirty-six consecutive fractures in 332 patients met inclusion criteria. These patients were divided into 2 cohorts. Group 1 (169 fractures) consisted of patients treated before the initiation of a standardized IV acetaminophen perioperative pain control protocol, and group 2 (167 fractures) consisted of those treated after the protocol was initiated. Results: Group 2 had a statistically significant shorter mean length of hospital stay (4.4 vs 3.8 days), lower mean pain score (4.2 vs 2.8), lower mean narcotic usage (41.3 vs 28.3 mg), lower rate of PT sessions missed (21.8% vs 10.4%), and higher likelihood of discharge home (7% vs 19%; P ≤ .001). Use of IV acetaminophen was also consistently and independently predictive of the same variables ( P < .01). Conclusion: The utilization of scheduled IV acetaminophen as part of a standardized pain management protocol for geriatric hip fractures resulted in shortened length of hospital stay, decreased pain levels and narcotic use, fewer missed PT sessions, and higher rate of discharge to home. Level of Evidence: Therapeutic level III.